Clinical features and short-term outcomes of patients with COVID-19 due to different exposure history. Issue 47 (20th November 2020) - Chen, Xianmeng; Wei, Wei; Cao, Jie; Hu, Xiaowen; Ryu, Jay Hoon
Abstract : Abstract: An ongoing outbreak of Coronavirus Disease 2019 (COVID-19) has spread around the world. However, the clinical characteristics and outcomes of patients with COVID-19 related to different modes of exposure have not been well defined. We aimed to explore the clinical features and outcomes of COVID-19 related to one-time community exposure versus continuous household exposure. Retrospective case–control study involving COVID-19 patients admitted to a tertiary designated center in China was performed. Patients were enrolled if they had known exposure history of one-time community exposure or continuous household exposure. Twenty patients were compared in terms of demographic characteristics, clinical presentation, chest CT images, laboratory results, treatments, and clinical outcomes at 1-month follow-up. There were 10 patients in one-time community and continuous household exposure groups respectively. Males compromised 80% and 40% while the median ages were 37.5 and 51 years old in the 2 groups, respectively. Fever and cough were most common symptoms. Ground-glass opacities were presented on chest CT scan in 90% and 70% of the patients, and the median CT scores were 7 and 16 on admission, respectively. Three patients ranked severe in the community exposure group while 7 patients were severe or critical in household exposure group. On 1-month follow-up, all patients were improved clinically but COVID-19 IgG antibody detected positive. Median follow-up CT scores were 0 and 13 while pulmonary function test abnormalities were 0/9 and 2/7 in the 2 groups, respectively. COVID-19 patients with one-time community exposure tended to be mild in severity and had better outcomes, comparing to those with continuous household exposure.